EFEKTIVITAS HASIL PEMBELAJARAN PADA MATA PELAJARAN EKONOMI SECARA DARING SELAMA PANDEMI COVID-19 KELAS XII IIS DI SMA ISLAM BAWARI PONTIANAK - Andri, Allif Fullah; Genjik, Bambang; Okianna, Okianna (Universitas Tanjungpura, 2023)
Learning effectiveness is a standard for achieving learning objectives by taking into account the indicators assessed. In 2020, learning activities must be carried out online due to the current condition of the Covid-19 pandemic. This decision is a new challenge for all educational units. Constraints and obstacles faced by both teachers and students, and of course can affect the process of teaching and learning activities. This study aims to determine the effectiveness of learning outcomes in online economics subjects during the Covid-19 pandemic for class XII IIS at Bawari Islamic High School Pontianak. This study uses a descriptive qualitative approach in finding research results. The results of the research were collected and concluded through interviews and documentation to the sample, namely economics education teachers in class XII and students in class XII IIS I. The results showed that the online economics learning process in class XII IIS I proved to be less effective in terms of delivering learning material and understanding of participants educate. So, this ineffective learning causes a decrease in the value of learning outcomes.